The Effect of Ibn Aqil Al-Hanbali's Disagreement with the Hanbali Jurisprudence in the Application of the Rule of Blocking the Pretext (Sadd Al-Dhara'i): An Analytical Jurisprudential Study - Hadi, Shahad Ahmad Abdullah (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This research aims to highlight the unique methodology of Ibn Aqil Al-Hanbali in the principles of Islamic jurisprudence, particularly in how he diverged from his school of thought regarding the principle of blocking the means (Sadd al-Dhara'i). This divergence has raised many questions concerning the jurisprudential rulings and the implications of these differences. The study seeks to elucidate Ibn Aqil's approach towards this principle. Methods: The research adopts an inductive, deductive, and analytical approach by examining cases where Ibn Aqil disagreed with the Hanbali school when invoking Sadd al-Dhara'i. It then analyzes and deduces the methodology he followed in these instances. Results: The study concludes that Ibn Aqil, a renowned jurist within the Hanbali school, had a distinctive methodology that differed from his own school. He often diverged from the Hanbali position on the principle of Sadd al-Dhara'i, which led to differing jurisprudential rulings. The study highlights that Ibn Aqil’s methodology was based on the higher objectives of Sharia (Maqasid al-Sharia), principles of jurisprudence, and linguistic implications. Conclusions: There is a need to re-examine the views and methodologies of jurists concerning controversial evidence, to better understand their unique approaches and the potential diversity within Islamic jurisprudential schools.